A systematic review and meta-analysis of social media's influence on mental health, family functioning, and visual content - Bdour Alwuqaysi (Social Sciences and Humanities Open, 2025)
The influence of social media on mental health, family functioning, and visual content exposure has grown rapidly, raising significant public health and societal concerns. This systematic review and meta-analysis synthesised findings from 60 peer-reviewed studies published between 2000 and 2024, identified through MEDLINE and ISI Web of Science without language restrictions. Studies were selected based on alignment with three predefined components: mental health outcomes, family dynamics, and the effects of visual content. Statistical analyses, including subgroup and text-based methods, revealed both beneficial and adverse effects. While social media fostered connectivity and emotional support, it also contributed to cyberbullying and reinforced inequalities, particularly among females. Clustering techniques further identified cross-variable patterns. These findings highlight the complex, multidimensional impact of social media and emphasize the need for targeted interventions to mitigate risks and support digital well-being.